Heterogenized vanadyl cations over modified silica surfaces: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous and amorphous silica supports - Shylesh, S.; Singh, A. R. (Journal of Catalysis, 2006)
Using a postsynthesis grafting method, 3-aminopropyltriethoxysilane (3-APTS) was functionalized over silica gel and mesoporous silica materials like SBA-15 and MCM-41. Vanadyl cations were then immobilized over the functionalized amino groups of the silica samples and used as a catalyst in the liquid-phase oxidation reaction of cyclohexane. Elemental analysis, PXRD, TEM, N-2 adsorption-desorption isotherms, FTIR, C-13 and Si-29 MAS NMR, UV-vis, and EPR techniques were used to characterize the developed materials. Characterization results suggest that the percentage of 3-APTS grafting depends on the number of isolated and genlinal silanol sites of the support material, the solvents used during the grafting reactions, and the sample pretreatment conditions. We found that using toluene as the dispersing medium and Si-MCM-41 as a support provides the maximum amount of amine functionalization, and thereby the highest percentage of vanadium immobilization. Catalytic activity and metal leaching studies show that vanadium-immobilized mesoporous solids are more active and stable than the silica gel-functionalized vanadium catalyst and a framework-substituted V-MCM-41 catalyst. The enhanced activity and stability of the immobilized vanadium catalysts compared with the V-MCM-41 and silica gel samples are attributed to the active metal site isolations, as well as to the spatial restrictions imparted from the concave silica surfaces of the mesoporous solids rather than the convex silica surfaces of the silica gel sample. (c) 2006 Published by Elsevier Inc.
Keywords: 3-APTS; mesoporous solids; Oxidation; Silica gel; Vanadium